Sequencing Effects of Object Control and Locomotor Skill During Integrated Neuromuscular Training in 6- to 7-Year-Old Children. Issue 8 (August 2019) - Duncan, Michael J.; Hames, Thomas; Eyre, Emma L.J.
Abstract : Abstract: Duncan, MJ, Hames, T, and Eyre, ELJ. Sequencing effects of object control and locomotor skill during integrated neuromuscular training in 6- to 7-year-old children. J Strength Cond Res 33(8): 2262–2274, 2019—This study examined whether scheduling of object control (e.g., throwing, catching) and locomotor skills (e.g., running, jumping), within an integrated neuromuscular training program, result in different responses in motor competence, muscular fitness, and perceived motor competence in 6- to 7-year-old children. Seventy-seven boys and 63 girls ( N = 140) from 3 primary schools were randomized into 3, 10-week interventions: Loco First ( n = 50) where locomotor skills were performed first followed by object control skills, Object First ( n = 48) where object control skills were performed first followed by locomotor skills, and a control group (CON) ( n = 42) who undertook school physical education. Results indicated greater total motor competence in Loco First and Object First vs. CON ( p = 0.001) with the increases in motor competence being greater for Object First vs. Loco First ( p = 0.001). Sprint speed (10 m) was lower for object first vs. CON ( p = 0.024). Standing long jump distance was greater in Loco First vs. CON ( p = 0.0001) and Object First ( p = 0.0001). Seated medicine ball throw distance was greater for Loco First and Object First vs. CON (both p = 0.001). Perceived motor competence was also higher for Object First vs. Loco First ( p = 0.005) and CON ( p = 0.001). This study suggests that scheduling object control skills before locomotor skills within school-based strength and conditioning has a greater effect on motor competence, muscular fitness, and perceived motor competence in 6- to 7-year-old children.